(untitled) (Ustozlar uchun, 2025)
Listening comprehension is one of the most essential skills in language learning, as it serves as the foundation for effective communication. The ability to understand spoken language influences learners’ speaking, reading, and writing skills. This article discusses the key issues in improving listening comprehension skills, including common difficulties faced by learners, the importance of listening in the educational process, and effective strategies for developing this skill. Special attention is given to modern teaching methods and the role of active listening in language acquisition.